Nootropic and anticonvulsant properties of the dry extract from Serratula Centauroides roots - I. V. Sviridov (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
The studies were carried out on white Wistar rats. The dry extract from Serratula centauroides L. was introduced to the animals at the doses of 50,100, and 150 mg/kg for 7 days prior to the testing. The nootropic effect of S. centauroides was estimated by using the test "conditioned passive avoidance reflex". In the groups of animals treated with the S. centauroides extract the number of animals with retained reflex was more than in the control group and the latent period of input into the dark bay of the device was longer than in the animals of the control group. The anticonvulsive activity of the S. centauroides extract was tested on the model of thiosemicarbazide-induced convulsions (30 mg/kg). It has been shown that the S. centauroides extract at the doses of 50-150 mg/kg prolongs the latent period of convulsion onset by 33% and increases the lifespan of the animals by 31-47% on the background of thiosemicarbazide-induced convulsions.